Exact Formulae for Degree Distance Indices of Sum Graphs - Muhammad Javaid; Faiz Farid; Jia-Bao Liu; Abdulaziz Mohammed Alanazi (Journal of Mathematics)
The degree distance index (DDI) is a vertex-degree weighted version of a well-known index that is called by Wiener index (WI). In extremal theory of graphs, improving the bounds with best possible values is a worth investigating problem. In this note, the exact formulae of the DDI for the four different types of the sum graphs in the terms of various indices of their factor graphs are computed. Moreover, a comparison is also presented between the obtained exact and already existing bounded values for the particular sum graphs.